Removal of Heavy Metals from Water Accompanied with Oil and Wastewater, Using Natural Dyes and Chemical Compounds.in Elwahate Jalu, Libya - Matter, Hamdy AB.; Ayad, Tariq M. (Scientific Journal of University of Benghazi, 2021)
Plants, whether leaves, fruits or bark, are characterized by an enormous number of organic compounds that can be used to form complexes with heavy and toxic elements that polluting the environment as these plant extracts are environmentally friendly compounds. In this paper, extracts from plants and the fruits like cloves, cinnamon bark, beet fruits, carrots, oranges, mint leaves, basil, Maringa, red cabbage, and sage have been performed. These extracts have shown different capabilities to precipitate many heavy ions dissolved in water, such as copper, cadmium, nickel, silver, lead, iron, chromium, calcium, zinc and manganese. Precipitation of heavy elements in their solutions. This could be applied to wastewater and water accompanied with oil and industrial waste water. Showing a high ability to precipitate these ions and follow the treatment process in all of its cases using a spectrophotometer.